Characteristics of perioptic and intraoptic arterial vascularization of extracranial segment of optic nerve - Radmila Balaban-Đurević; Samra Hajrović; Vanja Pljevaljčić; Valvita Reçi; Stefan Kulić; Milan Milisavljević; Siniša Šolaja (Биомедицинска истраживања, 2019)
Introduction: The optic nerve is supplied by the arterial branches of the supericial pial plexus and direct intraneural branches. The aim of the study was to study the morphological characteristics (origin, number of arteries, calibers, and branching pattern) of perioptic arterial vascularization and intraoptic vascular network of the extracranial sections of the optic nerve: canalicular and intraorbital. Methods: The study included 18 pairs of the optic nerves of both sexes (11 males and 7 females), aged 51 to 78 years, with no signs of changes in the structures of the nervous system. The vasculature of the optic nerves was microdissected and examined under the stereoscopic microscope, after injecting their arteries with 10% mixture of India ink and gelatin, and 5% formaline ixation. Results: The intracanalicular part of the optic nerve received ine blood vessels from the ophthalmic artery, usually in two branches in 29 (82.9%) cases, while in 6 (17.1%) specimens there was only one branch for the nerve. The intraorbital segment of the optic nerve was supplied by two interconnected systems of blood vessels, peripheral and axial, both coming from the central retinal artery. Conclusion: On the basis of the obtained results, it has been conirmed that both segments of the optic nerve have a rich and very delicate vascular network. The supericial pial arterial plexus of the intracanalicular segment of the optic nerve has been identiied as the only source of its vascular supply. The intraorbital part of the optic nerve has two interconnected systems of blood vessels: peripheral and axial.
Keywords: optic nerve; arteries; perioptic vascularization; intraoptic vascularization